Unexpected opportunities to support investor-state dispute prevention through the WTO Investment Facilitation for Development Agreement - Jansen Calamita (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
Mechanisms to avoid investment treaty disputes are an increasing priority for states. States often struggle, however, to develop evidence-based mechanisms due to a lack of information regarding the risks created by the operation of their administrative institutions. The self-assessment process of the WTO Investment Facilitation for Development Agreement provides states with a unique opportunity to develop information to strengthen dispute prevention efforts.
Keywords: 330